2019
DOI: 10.3892/etm.2019.8076
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoperitoneum in laparoscopy and preoperative antihypertensive agents: A retrospective study

Abstract: The purpose of the current study was to investigate the effects of preoperative antihypertensive agents on blood pressure (BP) changes after intraperitoneal CO 2 insufflation during laparoscopic surgery. The medical records of patients (≥50 years old) undergoing laparoscopic colon surgery were retrospectively analyzed (n=342). The patients were divided into four groups: normotensive group (group N), monotherapy with angiotensin receptor blockers (ARBs) (group A), monotherapy with calcium channel blockers (CCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In addition, studies in man have provided evidence that CO 2 insufflation of the peritoneum can result in increased blood pressure via increased catecholamine production, plasma renin activity, antidiuretic hormone production, and systemic vascular resistance 28 . Kim et al 29 found that standard laparoscopic CO 2 insufflation of the peritoneum resulted in a mean increase in systolic pressure of 21 ± 24 mm Hg in patients that were normotensive preoperatively. Insufflation of the peritoneal cavity to a pressure lower than 15 mm Hg can result in increased venous return from compression of the splanchnic circulation and subsequent increase in cardiac output and systemic arterial pressure 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in man have provided evidence that CO 2 insufflation of the peritoneum can result in increased blood pressure via increased catecholamine production, plasma renin activity, antidiuretic hormone production, and systemic vascular resistance 28 . Kim et al 29 found that standard laparoscopic CO 2 insufflation of the peritoneum resulted in a mean increase in systolic pressure of 21 ± 24 mm Hg in patients that were normotensive preoperatively. Insufflation of the peritoneal cavity to a pressure lower than 15 mm Hg can result in increased venous return from compression of the splanchnic circulation and subsequent increase in cardiac output and systemic arterial pressure 30 .…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the similar surgical duration in both groups in our study, implying a comparable duration of exposure to inhalant anesthetic agents with potential blood pressure-lowering effects ( 32 , 33 ). In general, CO 2 insufflation during laparoscopic abdominal surgery has been associated with elevated arterial blood pressure ( 34 , 35 ). However, with intra-abdominal CO 2 pressure set at 8 mm Hg, no differences were found in persistent systemic hypertension or borderline hypertension during LA or OA in our study.…”
Section: Discussionmentioning
confidence: 99%